Chaos walking [videorecording (DVD)] - Holland, Tom, 1996-; Mikkelsen, Mads, 1965-; Ridley, Daisy, 1992-; Bichir, Demián, 1963-; Erivo, Cynthia, 1987-; Jonas, Nick; Ness, Patrick, 1971- (Lionsgate, 2021)
In the not too distant future, Todd Hewitt discovers Viola, a mysterious girl who crash lands on his planet, where all the women have disappeared and the men are afflicted by 'the Noise,' a force that puts all their thoughts on display. In this dangerous landscape, Viola's life is threatened, and as Todd vows to protect her, he will have to discover his own inner power and unlock the planet's dark secrets.